CPTP: A sphingolipid transfer protein that regulates autophagy and inflammasome activation. Issue 5 (4th May 2018) - Mishra, Shrawan Kumar; Gao, Yong-Guang; Deng, Yibin; Chalfant, Charles E.; Hinchcliffe, Edward H.; Brown, Rhoderick E.
ABSTRACT: The macroautophagy/autophagy and inflammasome pathways are linked through their roles in innate immunity and chronic inflammatory disease. Ceramide-1-phosphate (C1P) is a bioactive sphingolipid that regulates pro-inflammatory eicosanoid production. Whether C1P also regulates autophagy and inflammasome assembly/activation is not known. Here we show that CPTP (a protein that traffics C1P from its site of phosphorylation in the trans -Golgi to target membranes) regulates both autophagy and inflammasome activation. In human epithelial cells, knockdown of CPTP (but not GLTP [glycolipid transfer protein]) or expression of C1P binding-site point mutants, stimulated an 8- to 10-fold increase in autophagosomes and altered endogenous LC3-II and SQSTM1/p62 protein expression levels. CPTP depletion-induced autophagy elevated early markers of autophagosome formation (Golgi-derived ATG9A-vesicles, WIPI1), required key phagophore assembly and elongation factors (ATG5, ATG7, ULK1), and suppressed MTOR phosphorylation and that of its downstream target, RPS6KB1/p70S6K. Wild-type CPTP overexpression exerted a protective effect against starvation-induced autophagy. In THP-1 macrophage-like surveillance cells, CPTP knockdown induced not only autophagy but also elevated CASP1/caspase-1 levels, and strongly increased IL1B/interleukin-1β and IL18 release via a NLRP3 (but not NLRC4) inflammasome-based mechanism, while only moderately increasing inflammatory (pyroptotic) cell death. Inflammasome assembly and activation stimulated by CPTP depletion were autophagy dependent. Elevation of intracellular C1P by exogenous C1P treatment (instead of CPTP inhibition) also induced autophagy and IL1B release. Our findings identify human CPTP as an endogenous regulator of early-stage autophagosome assembly and inflammasome-driven, pro-inflammatory cytokine generation and release.